Model prediksi limbah oli (B3) kendaraan 5 tahun yang akan datang di Kabupaten Sukabumi - Budiman, Dana; Suswendi, Sandi; Paikun (Jurnal TESLINK : Teknik Sipil dan Lingkungan, 2021)
ABSTRACT The increasing of a transportation that is increasingly sped up from year to year which causes an increase in a motorized vehicle which will have an impact on the increase in vehicle waste that is released by the vehicle. The waste that is released is oil waste (B3) which is dangerous if it is not managed properly by the community and government. B3 waste is the residue from the processing of raw materials containing hazardous and toxic materials which due to their nature and / or concentration can directly pollute and damage the environment, as well as endanger the environment, health, the survival of humans and other living creatures. The results of this study can find out about the amount of vehicle waste issued throughout the Sukabumi district and predict the amount of vehicle waste in the next 5 years using the modeling prediction formula Yc = a + bX. Keywords: Vehicles, hazardous waste, prediction of vehicle waste, Prediction Model